Facile synthesis of acacetin and its derivatives. Issue 15 (1st August 2016) - Zhao, Yuan; Cai, Li; Sui, Qiang; Lin, Feng; Jiang, Wen; Chen, Jianli; Lu, Weigeng; Gao, Qi
Graphical abstract: Abstract: Acacetin, a O -methylated bioflavonoid isolated from the traditional Chinese medicine Xuelianhua ( Saussurea tridactyla ), is a promising orally effective atrium-selective antiarrhythmic agent for the treatment of atrial fibrillation (AF). Here we describe an efficient two-component method for the synthesis of acacetin and its derivatives.